THE INFLUENCE OF ARTIFICIAL INTELLIGENCE (AI) AND CLOUD COMPUTING TECHNIQUES ON COST MANAGEMENT IN THE FIELD OF SMART MANUFACTURING: AN INNOVATIVE METHOD IN MANAGEMENT ACCOUNTING IN IRAQ (World Economics and Finance Bulletin, 2025)
This study investigates the impact of cloud computing and artificial intelligence (AI) technologies on cost management practices in smart manufacturing within Iraq, focusing on two primary objectives. First, it identifies how these technologies transform traditional cost management approaches, emphasizing real-time data access and enhanced decision-making capabilities. Second, the research assesses new management accounting techniques that can be integrated with cloud and AI technologies to improve operational efficiency. Utilizing a quantitative methodology, the study surveyed 65 professionals and managers from smart manufacturing companies that employ these technologies. A questionnaire of 10 items developed and judged by a panel of doctors and experts from the same major (See appendix A at the end of this study). These ten items cover the research questions and are answered by the professionals and managers of the manufacturing sector in Iraq. The findings reveal that cloud computing and AI significantly enhance cost management practices by providing timely financial and operational insights, ultimately leading to improved efficiency and competitiveness in the Iraqi manufacturing sector
Keywords: cloud computing; cost management; decision-making